'You should have come back earlier': the divisive effect of Australia's COVID-19 response on diaspora relations. Issue 2 (3rd April 2022) - Larson, Anna
ABSTRACT: Australia is largely considered an immigrant-receiving country, however, it is estimated that over one million Australians are living overseas at any given time. Despite this, diaspora relations have never been particularly robust, the consequences of which have become particularly visible during the Covid-19 pandemic. Australia used a strict closed-border approach in handling the pandemic and, although effective at reducing the spread of the virus, it will be argued that this isolationist approach was at the detriment of diaspora relations. This paper uses the findings from in-depth interviews with Australians living overseas to demonstrate that the country's response to the Covid-19 pandemic created an intergroup divide between Australia and its expatriates. Social identity theory and the theory of intergroup threat will be used to support the findings that Australian expatriates became the 'outgroup', perceived as a realistic threat by the resident national 'ingroup'. Public fear of the virus and Australia's strict isolationist stance created a divide between those within the border, and those trying to get in. This paper provides the first-hand experiences and sentiments of Australian expatriates, while further research exploring the perspective of resident nationals is recommended to facilitate a more robust understanding of the topic.